2006
DOI: 10.1007/s11926-006-0049-8
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and clinical significance of antiphospholipid antibodies in rheumatoid arthritis

Abstract: Published data were reviewed to evaluate the occurrence of antiphospholipid antibodies (aPL) in rheumatoid arthritis (RA) patients and to investigate their clinical relevance in this population. The mean prevalence was calculated at 28% and the median was 22%. Few studies have found a relationship between aPL antibodies and thrombosis, particularly in combination with other risk factors. Conflicting results have been reported on the association of anticardiolipin (aCL) antibody positivity and neurologic sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…RA patients might have additional underlying VTE pathophysiology, such as inflammatory damage to the vessel wall due to venulitis or presence of antiphospholipid antibodies. As the reported prevalence of antiphospholipid antibodies among RA patients has ranged from 5% to 75%,36 42 their contribution to the observed VTE risk is potentially substantial.…”
Section: Discussionmentioning
confidence: 99%
“…RA patients might have additional underlying VTE pathophysiology, such as inflammatory damage to the vessel wall due to venulitis or presence of antiphospholipid antibodies. As the reported prevalence of antiphospholipid antibodies among RA patients has ranged from 5% to 75%,36 42 their contribution to the observed VTE risk is potentially substantial.…”
Section: Discussionmentioning
confidence: 99%
“…18 Although the presence of aPL in RA patients was previously investigated, no significant association with APS manifestations was evident. [15][16][17] Most cited studies had small numbers of subjects and only one or two subtypes of aPL were assayed. Moreover, the cut-off value of aCL IgG or IgM did not meet the medium-to-high titre GPL and MPL levels of 40 used in the present work and, in some studies, aPL positivity was determined on the basis of the result of a single time point.…”
Section: Discussionmentioning
confidence: 99%
“…14 It was reported that aPL were present in 5-75% of RA patients. 15 Such wide variation in prevalence may be attributable to differences in the subtypes of aPL measured, measurement techniques, cut-off values, and particular characteristics of the subject populations. However, no significant association between the presence of aPL and APS manifestation in RA patients was found in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…A secondary APS will be developed in 30% of SLE patients [10]. In patients with rheumatoid arthritis a mean prevalence of 28% was reported [12]. Venous thrombosis can affect the vessels of any organ and is the most common manifestation of APS, followed by cerebral ischemia in the form of strokes and transient ischemic attacks [5].…”
Section: Epidemiologymentioning
confidence: 99%